Generational Differences in Attitudes towards Gender Roles and Violence Against Women - Aliye Dogan Gangal; Yaren Yigit and Yildiz Ali (Professor Despina Sapountzi-Krepia, 2024)
Generational Differences in Attitudes towards Gender Roles and Violence Against Women